Tunable data hiding in partially encrypted H.264/AVC videos - Xu, Dawen; Wang, Rangding; Zhu, Yani (Journal of visual communication and image representation, 2017)
•The encryption of Luma IPMs is designed in addition to residual and motion vector.•Data embedding is done on encrypted videos, which preserves the confidentiality.•The bin-strings of abs_level and abs_MVD are exploited for data hiding flexibly.•The hidden data can be extracted either in encrypted domain or decrypted domain. An improved scheme of data hiding directly in partially encrypted H.264/AVC videos using CABAC bin-string substitution is proposed. The encryption of Luma prediction modes is designed in addition to residual encryption and motion vector encryption in order to significantly improve the structural deterioration. Both the bin-strings of abs_level and the bin-strings of abs_MVD are exploited for data hiding to provide a higher flexibility for users to select the tradeoff between hiding capacity and video quality. Since the data embedding is done in the encrypted domain, the proposed scheme preserves the confidentiality of video content. With an encrypted video containing the hidden data, the receiver can accomplish data extraction directly in encrypted domain using only the data-hiding key, or obtain a decrypted video similar to the original version using only the cryptographic key. Experimental results have demonstrated that the proposed scheme can achieve better scrambling performance and higher embedding capacity.